Région n° 2... et France entière : Ain, Basses-Alpes, Hautes-Alpes, Alpes-Maritimes, Bouches-du-Rhône, Corse, Drôme, Isère, Savoie, Haute-Savoie, Var, Vaucluse - Lesage, Adolphe-Auguste (1862-1952)
fig., cartes, graph., tabl.